The Role of Simulation Educational Technologies in Teaching Doctors - М. Р. Potapov (Высшее образование в России, 2019)
In modern conditions, doctor as a specialist is faced with a large list of requirements fixed both in legal norms and in the rules of social behavior. The emergence of complex medical equipment and technologies, changes in the moral and legal conditions in the “doctor–patient” relationships led to the modernization of the medical training system. Especially it concerns the segment of practical specialist training. Simulation technologies in this sense should occupy an important place in medical education improving the quality and effectiveness of practice-oriented specialist training, reducing the risk of negative effects of the former education system in medical universities. The first experience of introducing such technologies into the training system at Yaroslavl State Medical University and in the country as a whole, along with obvious positive results, highlighted some problems. Their systematic solution is an important forward-looking task in the framework of the ongoing reform of medical education.